2011
DOI: 10.2478/v10153-011-0056-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker Profile of Minor Physical Anomalies in Schizophrenia Patients

Abstract: AIM: The aim of this study was to determine the frequency and topographical distribution of minor physical anomalies (MPAs) in schizophrenia patients and control subjects, and the ability of the items of the Waldrop scale to predict the patient-control status. MATERIAL AND METHODS: 128 schizophrenic patients (66 men, 62 women) and 103 normal controls (49 men, 54 women) were evaluated for MPAs with a modifi ed version of the Waldrop scale. RESULTS: Compared with controls, schizophrenia patients showed a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 9 publications
3
16
1
Order By: Relevance
“…Six minor malformations were significantly more common in the group of schizophrenia patients than in the control group: fine hair, two or more hair whorls, high palate, furrowed tongue eyebrows fused, wide nose basis (p < 0.01). Most studies showed furrowed tongue to be a significant marker of schizophrenia without respect to the type of furrows; Scutt et al [24] reported higher rate of large tongue, while other studies scored randomly furrowed tongue, transversely furrowed tongue or tongue with smooth-rough spots [25]. Our study revealed significantly higher prevalence of only one tongue features type in schizophrenic patients: vertical fissure running along the midline and few fissures diffusely distributed cross the dorsal tongue surface (15.9 vs. 2.4%).…”
Section: Discussionmentioning
confidence: 99%
“…Six minor malformations were significantly more common in the group of schizophrenia patients than in the control group: fine hair, two or more hair whorls, high palate, furrowed tongue eyebrows fused, wide nose basis (p < 0.01). Most studies showed furrowed tongue to be a significant marker of schizophrenia without respect to the type of furrows; Scutt et al [24] reported higher rate of large tongue, while other studies scored randomly furrowed tongue, transversely furrowed tongue or tongue with smooth-rough spots [25]. Our study revealed significantly higher prevalence of only one tongue features type in schizophrenic patients: vertical fissure running along the midline and few fissures diffusely distributed cross the dorsal tongue surface (15.9 vs. 2.4%).…”
Section: Discussionmentioning
confidence: 99%
“…MPAs are insignificant, fixed physical defects or deviations in appearance from essential physical characteristics and are of little functional significance (Tarrant and Jones, 1999). Although MPAs have been suggested to be associated with other neurodevelopmental and behavioral disorders, including but not limited to attentional disorders, autism, fetal alcohol syndrome, learning disabilities, and sensory impairment in general (Compton and Walker, 2009), the pattern of changes in these morphological characteristics, especially higher frequency, has been suggested to reflect neurodevelopmental defects that allow better characterization of schizophrenia patient subgroups (Akabaliev et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Neurodevelopmental hypothesis provides a valuable framework for genetic studies of endophenotypes in schizophrenia (Owen et al, 2011;Braff and Light, 2005). defects that allow better characterization of schizophrenia patient subgroups (Akabaliev et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Below we provide a detailed description of the domestication traits commonly found in schizophrenic patients ( Fig. 1 Physical Anomalies SZ patients typically feature minor craniofacial dysmorphisms, including facial asymmetries, particularly those arising along the midfacial junctions [between frontonasal and maxillary prominence derivatives; Gourion et al, 2004, Deutsch et al, 2015, and ear shape abnormalities [including adherent ear lobes, lower edges of the ears extending backward/upward, malformed ears, asymmetrical ears, or cuspidal ears; Yoshitsugu et al, 2006;Akabaliev et al, 2011;Lin et al, 2012] are reproducibly observed in SZ patients. Some of these features (like a prominent crux of helix and ear lobe crease or a primitive shape of the ear) are considered pathognomonic for SZ in the differential diagnosis of psychotic conditions [Trixler et al, 2001;Praharaj et al, 2012].…”
Section: Domestication Features In Szmentioning
confidence: 99%